Kepuasan Belajar Bahasa Inggris Online di Madrasah Aliyah (Sekolah Tinggi Islam): Tinjauan Literatur - Zalsa Bella, Herlina Auriellas; Made Hery, Santosa (Universitas Nusantara PGRI Kediri, 2023)
The Covid-19 pandemic affects every sector of human life, including the education system. Satisfaction is the positive feeling of humans related to the process of doing or making something and during the pandemic, this aspect can be affected especially in the education field with online learning. It is an important aspect that affects students’ results in how they understand the material, do the evaluation, and get the best result from it. The study aimed to fulfill the need for information and reference material for researchers, teachers, and other Islamic schools for further research. The design of this literature review article used thematic analysis to give guidance and overview insight between analyzed studies and connection theory. The theory includes several factors based on Elshami’s theory of the intrinsic values of the students (interaction and outcomes) and also the extrinsic factors (instructor, technology, and learning media). The researcher finds related articles and selected them from 16 articles to 7 articles. The result shows that students' satisfaction relies a lot on external factors; teachers' skills, learning media, and technology during the EFL learning process. Based on this, institutions and teachers can find out solutions to solve the problem for future preparation in learning.